Analysis of The Delay in The Implementation of Toll Road Project Work - Jati Irawan (Eduvest - Journal of Universal Studies, 2025)
Infrastructure development is crucial for economic progress, and Indonesia has witnessed significant advancements in this sector, especially in toll road projects over the past decade. The Indonesian government, through the Ministry of Public Works and Housing (PUPR), is dedicated to infrastructure development to achieve the "Golden Indonesia" 2045 vision. Despite this commitment, many projects face delays, adversely affecting costs, quality, and timelines. This study investigates the causes of delays in toll road projects with case studies on two projects in Sumatra, one in Java, and one in Kalimantan. The research methods include literature review, data collection, and surveys distributed to project owners, supervision consultants, and contractors, followed by analysis of the survey results. Among 24 respondents, the predominant delay factors identified are unresolved land issues, improper scheduling, resource shortages, and unforeseen circumstances. Further analysis revealed that among the 16 delay causes related to land, five stem from non-technical aspects and 13 from technical aspects, with overlapping causes such as incomplete contract work types and unforeseen situations. The average risk value indicates that land-related delay factors have a higher impact compared to others. Specifically, the technical aspect risk value is 10.75, and the non-technical aspect is 12.33 on a maximum risk value scale of 25. These results highlight the critical need for effective land risk management to enhance efficiency and effectiveness in toll road project execution. This research aims to assist future project management, enrich civil engineering knowledge, and support the continuous growth of infrastructure development in Indonesia.